MASTER (Motivating, Acquiring, Searching, Triggering, Exhibiting, Reflecting) learning model in terms of literacy ability and students' mathematics learning motivation - Sabirin, Muhamad; Hidayatullah, Akbar; Saputri, Rinda Azmi; Atsnan, Muh. Fajaruddin; Nareki, Maisea Ledua (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2022)
It is argued that mathematical literacy skills might be improved when learning motivation is high. This study aims to examine the difference in mathematical literacy skills between students who joined a learning model that stimulate motivation, the MASTER learning model (Motivating, Acquiring, Searching, Triggering, Exhibiting, and Reflecting) and those who attended conventional learning in terms of high, medium, and low learning motivation. This is a quasi-experimental study with a population of all seventh-grade students of an Islamic Junior School in South Kalimantan, Indonesia. The sample was selected using the purposive sampling technique with group VII A as the experimental class and group VII E as the control class. The instrument used was a test of students' mathematical literacy skills and a student's learning motivation questionnaire. The data were analyzed using a two-way ANOVA. The results showed that: (1) there were differences in mathematical literacy skills between students who attended the MASTER learning model and those who took conventional learning; (2) there were differences in mathematical literacy abilities between students with high, medium, and low motivation to learn, and (3) there was an interaction between the MASTER learning model and learning motivation on students' mathematical literacy abilities.